THE EFFECT OF GUIDED IMAGINATION TECHNIQUES ON HYPERTENSION IN THE ELDERLY IN THE KUTABUMI VILLAGE, TANGERANG - Selvy Afrioza; Febrilya Mustika; Bela Novita Amaris Susanto (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2023)
Background: Hypertension is categorized as a non-communicable disease and nicknamed The Sillent Killer. Uncontrolled hypertension is a major contributor to heart disease, stroke and kidney failure. Based on a preliminary study in Kutabumi Village, Tangerang Regency with 155 residents, there were 55 participants aged between 46 and 65 years old who had a history of hypertension. Efforts to reduce blood pressure include a healthy lifestyle, blood pressure control, pharmacological and non-pharmacological treatment. Objective: the purpose of this study is to determine the influence of guided imagination techniques on hypertension in the early and late elderly in Kutabumi Tangerang Village Method: This study used the quantitative method Quasi Experiment One Group Pretest-Posttest with Instrument observation sheets totaling 50 respondents, Shapiro Wilk Normality test, Wilcoxon signed rank test and Mann-Whitney Test. Results: This study showed that p value decreased after the treatment of guided imagination techniques. The result of the p value of systolic hypertension after treatment is p ≤ 0.05 means a significant decrease, while the result of the p value of diastolic hypertension after treatment has decreased ≥ 0.05 means that diastolic blood pressure does not experience a meaningful decrease after being given a guided imagination technique treatment. Conclusion: this study has an influence on the treatment of guided imagination techniques on reducing hypertension in the elderly in Kutabumi Tangerang Village.